The "Imperfect Victim" in the Media Construction: The Relationship between Public Opinion and the Image of the Victim Media Coverage Research - Wu, Yidan (International Journal of Social Sciences and Public Administration, 2024)
In order to explore the hidden infringement of ' imperfect victims ' under the unequal relationship of power and the way of media coverage of such incidents, this paper takes the ' Wuhan falling mother ' incident as an example to study the secondary damage suffered by the imperfect victim when there is a deviation between the image of the victim and the public opinion and the universal view of the media. According to the analysis, such victims are more vulnerable to hidden infringement under a specific power structure. Therefore, it is suggested that the media should adopt a more sensitive and responsible attitude when reporting such public crisis events, so as to prevent similar incidents from happening again and causing further harm to the victims.